2017
DOI: 10.1007/s11103-017-0629-1
|View full text |Cite
|
Sign up to set email alerts
|

Herbaspirillum rubrisubalbicans, a mild pathogen impairs growth of rice by augmenting ethylene levels

Abstract: Herbaspirillum rubrisubalbicans decreases growth of rice. Inoculation of rice with H. rubrisubalbicans increased the ACCO mRNA levels and ethylene production. The H. rubrisubalbicans rice interactions were further characterized by proteomic approach. Herbaspirillum rubrisubalbicans is a well-known growth-promoting rhizobacteria that can also act as a mild phyto-pathogen. During colonisation of rice, RT-qPCR analyses showed that H. rubrisubalbicans up-regulates the methionine recycling pathway as well as phyto-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…seropedicae showed induction of ascorbate peroxidases 35 , though the genes encoding these enzymes were not affected in our RNA-seq analyses. Moreover, seven days after inoculation, ROS levels in Herbaspirillum rubrisubalbicans attached to rice roots had increased suggesting that the bacteria were subject to oxidative stresses 36 . In this work, two peroxidase genes were induced by H .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…seropedicae showed induction of ascorbate peroxidases 35 , though the genes encoding these enzymes were not affected in our RNA-seq analyses. Moreover, seven days after inoculation, ROS levels in Herbaspirillum rubrisubalbicans attached to rice roots had increased suggesting that the bacteria were subject to oxidative stresses 36 . In this work, two peroxidase genes were induced by H .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Valdameri et al . 36 detected induction of ACC oxidase in rice plants inoculated with the pathogen H . rubrisubalbicans .…”
Section: Resultsmentioning
confidence: 99%
“…Among the Streptomyces(Viaene et al, 2016), S. lividans can protect plants against fungal pathogens(Meschke and Schrempf, 2010), while S. scabiei causes rot on roots and tubers of potatoes, beets, and carrots(Hiltunen et al, 2009). Members of the Herbasprillum rubrisubalbicans species are usually mild pathogens in sugarcane, sorghum, and rice(Valdameri et al, 2017), while H. seropedicae and some strains of…”
mentioning
confidence: 99%
“…However, few proteomics studies have identified bacterial proteins related to nitrogen fixation or nitrogen metabolism during grass colonization. Only two proteomics studies have identified proteins involved in nitrogen fixation and ammonium assimilation, NifH and glutamine synthetase (GS), respectively, which are up-regulated in rice roots colonized by the H. seropedicae SmR1 (Alberton et al, 2013) or the H. rubrisubalbicans M1Sm300 (Valdameri et al, 2017). These findings suggest that the cells are under nitrogen-fixing conditions after 7 days of inoculation.…”
Section: Proteome and Biological Nitrogen Fixation In Grassmentioning
confidence: 99%